Penerapan Metode Economic Order Quantity Dalam Mewujudkan Efisiensi Biaya Persediaan STUDI KASUS PADA PT. SETIAJAYA MOBILINDO BOGOR - Herawan, Chandra; Pramiudi, Udi; Edison, Edison (Institut Bisnis dan Informatika Kesatuan, 2013)
Inventories are important in making sales for the company to meet consumer demand, so asexpected to be able fill up market needs and utilize existing opportunities to earn income. Ownedstock company must supply the optimum value, so as to meet every demand with minimum cost.then the company can use the method of economic order quantity (EOQ) calculation of theoptimum amount of inventory. By using the EOQ method is the cost incurred for the procurementof supplies to be more minimal. The purpose of this study was to determine how theimplementation of the EOQ method and inventory costs that occurred in the company, as well as tofind out how the role of the EOQ method in the company stock cost efficiently. Research on theauthor is in the PT. Setiajaya Mobilindo Bogor. PT. Setiajaya Mobilindo Bogor is a companywhich engaged in sales, service and spareparts. The results obtained by the method of economicorder quantity (EOQ) ordering the company to find out how economical for each inventory itemand find out the frequency of bookings for a period and when ordering goods to be redone, so thedemand for goods can be satisfied in the maximum. Thus the economic order quantity (EOQ)method important to act in efficient of suppy cost in that company.